THE INNOVATIVE LEARNING MANAGEMENT IN ECONOMICS TO IMPROVE STUDENT’S LEARNING ACHIEVEMENT AT STATE SENIOR HIGH SCHOOL 1 OF BANDA ACEH - Cut Hayatun Zohra; Djailani AR; Khairuddin . (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2014)
Abstract: Innovative learning management on Economics in Senior High School is a right choice for teacher because Economics should be managed professionally including planning, implementation and evaluation. This study aimed to find out the planning, implementation, evaluation, and problems faced by teachers when implemented Innovative Learning Management in Economic at Senior High School 1 of Banda Aceh. The research method used was descriptive method with qualitative approach. Techniques of data collection used were observation, interview, and documentation study. The research subjects were principal, Economic teachers, and students. The results showed that the innovative lesson plan, which was planned by teachers through observing, ask, collect data, associate and communicate material that has been determined, was oriented to the curriculum in 2013 and arranged in the form of Learning Implementation Plan (RPP) and learning orientation was adjusted to the level of education (Senior High School). In arranging the Lesson Implementation Plan of curriculum in 2013, teachers referred to four core competencies including religious affective, social affective, cognitive and psychomotor aspects that should be by every student. Learning was implemented by using learning innovative concept with a variety of learning in the inside and outside classroom, as well asusing contextual learning model. Evaluation of innovative learning was conducted witht wo evaluations, learning process evaluation and the learning outcomes evaluation. There are two inhibiting factors in implementing innovative learning, namely: the variety ability of learners and the teachers do not maximize the use of learning media to support the learning process.Keywords: Learning management and Innovative learning concept.Abstrak: Manajemen pembelajaran inovatif pada mata pelajaran ekonomi di Sekolah Menengah Atas merupakan suatu pilihan yang tepat dilakukan oleh guru, karena mata pelajaran ekonomi merupakan salah satu mata pelajaran yang harus dikelola secara profesional yang meliputi perencanaan, pelaksanaan dan evaluasi. Tujuan penelitian ini untuk mengetahui perencanaan, pelaksanaan, evaluasi dan hambatan-hambatan yang dihadapi oleh guru ketika melaksanakan proses pembelajaran inovatif pada pelajaran ekonomi di SMA Negeri 1 Banda Aceh. Metode penelitian adalah metode deskriptif dengan pendekatan kualitatif. Teknik pengumpulan data adalah observasi, wawancara, dan dokumentasi. Subjek penelitian adalah kepala sekolah, guru mata pelajaran ekonomi, dan siswa. Hasil penelitian menunjukkan bahwa perencanaan pembelajaran inovatif direncanakan oleh guru melalui mengamati, menanya, mengumpulkan data, mengasosiasi dan mengkomunikasikan materi yang telah ditentukan. Semua kegiatan tersebut direncanakan guru sesuai dengan pedoman kurikulum 2013, dan orientasi pembelajaran disesuaikan dengan tingkat pendidikan (Sekolah Menengah Atas). Dalam penyusunan RPP Kurikulum 2013, guru mempedomani empat kompetensi inti yang hendak dicapai dalam pembelajaran yang meliputi kompetensi tentang sisi afektif keagamaan, sisi afektif prilaku sosial, sisi kognitif dan sisi psikomotor yang harus dimiliki oleh setiap siswa. Pelaksanaan pembelajaran dilaksanakan dengan menggunakan konsep pembelajaran inovatif yang dilakukan oleh guru dengan pembelajaran yang bervariasi di luar dan di dalam kelas, serta menggunakan model pembelajaran kontekstual. Evaluasi pembelajaran inovatif dilaksanakan dengan dua evaluasi, yaitu evaluasi proses pembelajaran dan evaluasi hasil pembelajaran. Ada dua faktor yang menghambat pelaksanaan pembelajaran inovatif, yaitu: kemampuan peserta didik yang beragam dan guru yang belum memanfaatkan media pembelajaran secara maksimal untuk mendukung proses pembelajaran.Kata Kunci: Manajemen Pembelajaran dan Konsep Pembelajaran Inovatif.